Antibiotic resistance profiles of biofilm-forming bacteria associated with urine and urinary catheters in a tertiary hospital in Ile-Ife, Nigeria - Michael O. Osungunna; Grace O. Onawunmi (Southern African Journal of Infectious Diseases, 2018)
Background: Microorganisms that infect humans differ in pathogenesis, virulence factors and antimicrobial resistance profiles. In natural settings, bacterial cells are most often found in close association with surfaces and interfaces, in the form of multicellular aggregates commonly called biofilms. Given their ubiquity and importance in the microbial world, it is hardly surprising that biofilms have attracted the attention of the scientific community. Biofilm formation on medical implant devices such as catheters is also a major problem that is closely tied to the adhesion and resistance-related abilities of the biofilm.